Effect of Human Resource Management Practices on Students’ Academic Performance in Public Secondary Schools in Machakos Sub-County, Machakos County, Kenya - Ndunda, Tiffany Ndanu; Mulwa, David M.; Muriungi, Pamella Karambu (IOSR Journal of Research & Method in Education, 2025)
The interest in school leadership is based on the belief it can significantly influence directly or indirectly, the teaching and quality of learning in schools, and as a result student achievement. This study sought to establish the effect of human resource management practices on students’ academic performance in public secondary schools in Machakos Sub-County, Machakos County, Kenya. The study was based on the human capital theory. A descriptive research design was used for this study. The target population for this study were 48 principals and 400 teachers totalling 448 respondents from which a sample of 15 principals and 120 teachers were chosen using simple random sampling. Questionnaires were used to collect data from the respondents. Validity was established through expert judgment. The research used Cronbach's alpha formula to test reliability. Cronbach’s alpha coefficient of 0.9641 was realized indicating the consistency of research instruments. Data collected were coded and analysed with the help of the Stata analysis package. Descriptive statistics in the form of mean and standard deviation were used to display the data. Inferential statistics specifically regression analysis was used to show the relationship and strength of the relationships among study variables respectively. The study found that human resource management practices had a positive and statistically significant effect on students’ academic performance. Based on the findings, the study recommends that in the aspect of human resource management practices, there is a need for the principal to recognize teachers who have contributed positively to improving the quality of education; principals ought to devise other ways of curriculum implementation practices which motivates the teachers and the students other than monitoring the classroom attendance of the teachers, regular internal assessments in the school, or even emphasizing covering the syllabus on time.
Keywords: Human Resource Management; Students’ Academic Performance; Public Secondary Schools